Innovations of history education in the High Schools, ICSS, Malaysia - Salleh, Mohamad Johdi; Ayudin, Ahmad Rafaai (Universiti Pendidikan Indonesia, Bandung, Indonesia, 2010)
European and Asian developed countries consider History as the main subject in elementary and high schools curriculum, which is professionally reinforced in higher education. This consideration is intended to ensure that people respect leader and community contribution to maintain and develop excellences of civilization in this country. One way or another, the position of some social science subjects, including history, in today’s education system are more challenged by foremost priority over sophisticated physical technology. Although it is considered as a central subject to take by high school students, its position will become vulnerable with loads of critics directed by those involved in the learning and teaching process, i.e. the students. Therefore, this paper focuses on discussion about the implementation of learning and teaching process of history from the aspects of philosophy, objectivity, the excellence of ’little historian’, principles, values and citizenship. Moreover, this paper presents the results of brief analysis towards Form Four and Form Five students in Gombak and Rawang, Selangor, Malaysia. It is expected that the presentation of this paper will produce an outcome in the objectivity of integrated, quality and professional curriculum of history, especially to develop a country in this globalization era on the basis of creativity and innovation of historical education.